'I Want to be New and Different. Anything I'm Not.' Accent-Mixing in Singing. Issue 2 (3rd April 2018) - Yang, James H.
Abstract : While Britpop singers often adopt the Mid-Atlantic accent (Trudgill, 1983) or what Simpson labels the 'USA 5 model', a number of recent pop singers have abandoned the American model in favour of their regional accents. In particular, some singers display the hybrid features of distinct English accents, as evidenced in Lenka Kripac, a world-famous pop singer from Sydney, who mixes various accents in her singing, although she speaks General Australian English when she talks in interviews. This evidence is based on the sound analysis of Lenka's 42 songs collected from all of her singles and albums, together with her responses in eight interviews in different countries. Her accent-mixing singing style is expounded as a 'referee design' for her hypothetical allegiances with her non-present fans speaking different varieties of English to promote her albums worldwide.